A Comparative Analysis of Public Trust in the Instagram Accounts @abouttng and @lapor_laksa in Accommodating Community Aspirations - Deokeny Indrawan (Journal of Human Interaction and Social Studies, 2026)
Public trust has become an essential factor in determining the effectiveness of digital communication platforms in accommodating community aspirations. This study aims to measure and compare the level of public trust in the Instagram accounts @abouttng, a community-based media platform, and @lapor_laksa, the official Instagram account of the Tangerang City Government, in facilitating public aspirations. The research employed a quantitative approach with a comparative design. Data were collected from 200 respondents, consisting of 100 followers of @abouttng and 100 followers of @lapor_laksa, selected through quota sampling and accidental sampling techniques. Public trust was measured through cognitive, affective, and behavioral dimensions, while hypothesis testing was conducted using the Independent Samples t-test. The findings revealed a significance value of 0.000, which was lower than the established significance level (α = 0.10), indicating that the null hypothesis was rejected and the alternative hypothesis was accepted. The results confirm a significant difference in public trust between the two Instagram accounts. Respondents generally perceived @abouttng as more responsive, transparent, interactive, and effective in managing public complaints and disseminating information than @lapor_laksa. These findings suggest that communicative performance plays a more decisive role in shaping public trust than formal institutional status within digital public communication environments.